Post-COVID-19 pandemic: what is next for the tourism sector in Malaysia? / Dr. Muhammad Hanif Othman and Zouhair Mohd Rosli - Othman, Muhammad Hanif; Mohd Rosli, Zouhair (Universiti Teknologi MARA, Kedah, 2023)
Tourism is one of the fastest-growing economic sectors in the world, with tourism growth consistently exceeding the global Gross Domestic Product (GDP) growth (WTTC, 2020). Before the COVID-19 pandemic, tourism contributed 10% of global employment and 10.3% of the world's GDP in 2019. Additionally, export earnings from international tourism reached USD1.7 trillion in the same year, which was equivalent to 7% of the total global export and 28% of the global services export (UNWTO, 2020). In Malaysia, tourism contributed about RM240 billion or 15.9% of the GDP and employed 3.6 million workers, which was equivalent to 24% of the total workforce in 2019. The highest employment within the tourism sector was recorded by the food & beverage serving (34.7%) and retail trade (32.5%) industries (DOSM, 2020). The COVID-19 pandemic has reversed the gains made from tourism activities. Malaysia's tourism contribution to the GDP declined from 15.9% in 2019 to 14.1% in 2020. The share of tourism employment also reduced from 23.6% to 23.1%, with 104,300 tourism workers losing their jobs during the same period. Inbound tourism expenditures declined by 85% to RM13.2 billion, the lowest recorded since 2000. Domestic tourism expenditures also declined, but at a lower rate, by 63%, to RM21.7 billion in 2020 (DOSM, 2022). In 2021, tourism had yet to recover to the pre-pandemic level of 2019. Globally, tourism contribution to the GDP remained lower than the 2019 level at 6.1% (USD 5.8 trillion) in 2021 compared to 10.3% (USD 9.6 trillion) in 2019. Similarly, employment remained 44 million short of the 333 million jobs at the pre-pandemic level (WTTC, 2022). Similar situation is reported in Malaysia; the local tourism has not bounced back to its prepandemic level. Instead, it has worsened due to a series of Movement Control Orders (MCOs) imposed in 2021. As a result, the tourism contribution to the GDP had decreased even further compared to 2020 (15.9%) to 12.8% in 2021. Although the share of tourism employment increased slightly above the 2020 level at 23.4%, it remains lower than the pre-pandemic level and short of 41,600 jobs. Inbound tourism expenditures were hit worse than domestic tourism expenditures. Consequently, for the first time since 2000, the share of domestic tourism expenditures was higher than inbound tourism expenditures in 2020 and 2021. Also, international and domestic tourism expenditures were 99.6% and 88% lower than in 2019 (DOSM, 2022). The future remains uncertain for the tourism sector worldwide, including in Malaysia. In September 2022, the majority (61%) of experts expected international tourism to recover in 2024 instead of 2023 due to new challenges of geopolitical tension between Russia and Ukraine, rising inflation, and a spike in oil prices, which has eroded consumer purchasing power and savings (UNWTO, 2022). Globally, policymakers have turned to domestic tourism activities to push tourism demand in the host country as the tourism industry is still in recovery (UNWTO, 2022). Similarly, while Malaysia continues to promote inbound tourism, building a resilient and sustainable domestic tourism demand is equally crucial. The focus should be on promoting domestic tourism activities to create a strong and reliable alternative to inbound tourism in generating receipts for the country. It will assist tourism recovery and ensure that the sector can survive future global health and economic shocks.